Renewable energy law : an international assessment / Penelope Crossley. - Crossley, Penelope (Cambridge University Press, 2019)
With the rapid growth of the renewable energy sector, it has become increasingly important to understand how renewable energy is defined in national laws around the world and what regulatory mechanisms these countries are deploying to achieve their renewable energy goals. In Renewable Energy Law: An International Assessment, Penelope J. Crossley compares the national renewable energy laws for each of the 113 countries that have such a law, shedding light on the question of whether energy laws are converging globally to facilitate trade or engaging in regulatory competition. The book includes over sixty extracts from different national laws, case studies on the European Union and the Chinese wind sector, and many examples of the particular challenges facing specific countries. This work should be read by scholars, policymakers, regulators, employees of commercial entities operating in the energy sector, and anyone else interested in the legal and regulatory landscape of renewable energy.